2, 4, 6-TCP removal mechanism in the process of leaching manganese. Issue 18 (12th December 2019) - Li, Haoran; Wang, Junjie; Feng, Yali; Yi, Aifei; Du, Zhuwei
ABSTRACT: 2, 4, 6-trichlorophenol (2, 4, 6-TCP) was used in the leaching system of manganese/pyrite to achieve the simultaneous utilization and removal of 2, 4, 6-TCP. When the initial concentration of 2, 4, 6-TCP was 300 mgL −1 and the weight percentage of pyrite was 12.8%, the removal of 2, 4, 6-TCP was 83.3%, meanwhile, the leaching efficiency of manganese was 97.6%. Fourier Transform Infrared Spectroscopy (FTIR) showed that the removal of 2, 4, 6-TCP mainly relied on the chemical oxidative degradation by Mn (IV) and the surface adsorption by leaching residue, including physical adsorption and chemical adsorption. Gas Chromatography–Mass Spectrometry analysis and Chemical Oxygen Demand (COD) indicated that 2, 4, 6-TCP was degraded to inorganic substances eventually.